Presurgical Evaluation of Impacted Mandibular Third Molar using Digital Fluoroscopy (Mustansiria Dental Journal, 2018)
Background: In order to evaluate the impacted mandibular third molar preparation there are many radiographic techniques used include conventional and digital techniques, the aim of the study is to establish the use of digital fluoroscopy in evaluation of impacted mandibular third molar.Material and Method: - Digital fluoroscopy and conventional bisecting line angle techniques were done for 20 Iraqi adult males 20 -25 years with class one normal occlusion according to angle classification. Measurements were done according to classification system which includes angulations relation to the ramous, depth of impaction, nature of overlying tissue, root morphology, relation to second molar, and its relation to inferior dental canal.Results: It was revealed that there are non significant differences in radiographic assessments of impacted mandibular third molar between digital fluoroscopy and conventional bisecting line angle technique for all classification systems of impacted mandibular third molar at P ≤ 0.01.Conclusion:-The value received from this study showed that digital fluoroscopy could be applied as a diagnostic tool in presurgical evaluation of impacted mandibular third molar.